2018
DOI: 10.22492/ijpbs.4.2.01
|View full text |Cite
|
Sign up to set email alerts
|

Brand Selection in Planned Purchasing: An Analysis of Asian User Behavior

Abstract: Users in planned purchasing undergo significantly different decision-making process compared to impulsive purchasing. Although several researchers have investigated user behavior of buying products from planned categories such as, organic products and halal products, research in the domain of selecting a specific brand within a category are limited. A qualitative study was conducted among users across several Asian markets such as China, Hong Kong, Taiwan, South Korea and Thailand to understand factors influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…Sebastian et al conducted a qualitative study among users in several Asian markets, including China, Hong Kong, Taiwan, South Korea, and Thailand, to understand the factors that influence the brand selection process in a planned buying environment. Qualitative research has shown that packaging has a positive impact on the user's brand selection process [13], while packaging rich in national culture has a stronger appeal.…”
Section: Introductionmentioning
confidence: 99%
“…Sebastian et al conducted a qualitative study among users in several Asian markets, including China, Hong Kong, Taiwan, South Korea, and Thailand, to understand the factors that influence the brand selection process in a planned buying environment. Qualitative research has shown that packaging has a positive impact on the user's brand selection process [13], while packaging rich in national culture has a stronger appeal.…”
Section: Introductionmentioning
confidence: 99%